Hubungan Pengetahuan dan Pendidikan Ibu Hamil dengan Anemia di rt 10 rw 8 Wilayah Kerja Puskesmas Kemalaraja Baturaja - Apria Wilinda Sumantri (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Iron deficiency anemia in pregnant women is still a public health problem in Indonesia because of its high prevalence. The main cause of this anemia is iron deficiency. During pregnancy there is an almost threefold increase in the need for iron for fetal growth and the needs of pregnant women. The aim of the study was to determine the relationship between the knowledge and education status of pregnant women and anemia in RT 10 RW 8 in the working area of the Kemlaraja Baturaha Health Center in 2020. The sampling technique used a cross sectional method with a total sample of 24 people. The variables studied and presented in the form of a frequency distribution table and tested with univariate and bivariate analysis, using questionnaires about knowledge and education with anemia. Research has been carried out on January 20 to February 17 2020, it was found that there was a significant relationship between knowledge variables and anemia, we can see this from the P value = 0.009, and there is a significant relationship between education variables and anemia, this can be seen from the result of the P value = 0.010. It is hoped that this research can become information material for health workers to more often check the hemoglobin level of pregnant women, especially if it has previously been known that the pregnant woman is low in sensitivity and for health agencies, especially officers at the Kemalaraja Health Center in an effort to improve education and knowledge of pregnant women.